Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1097/jto.0b013e31820b80ca
|View full text |Cite
|
Sign up to set email alerts
|

Foxp3+ Regulatory T Cells and Natural Killer Cells Distinctly Infiltrate Primary Tumors and Draining Lymph Nodes in Pulmonary Adenocarcinoma

Abstract: Accumulation of Tregs in the center of lung tumors and in metastatic lymph nodes in combination with a decrease in the natural killer cell numbers suggests a critical role of Treg in the formation of immunosuppressive tumor microenvironment. Therefore, lung cancer immunotherapy may be improved by a specific Treg elimination or suppression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 28 publications
3
47
2
Order By: Relevance
“…Tumor infiltration by Tregs, near-to-invariably detected by the immunohistochemical detection of FOXP3 + lymphocytes, has been associated with poor prognosis in cohorts of patients affected by multiple distinct neoplasms, including Hodgkin lymphoma, melanoma as well as breast, gastric and ovarian carcinoma [29, [91][92][93][94]. In line with these results, it has been shown that clinical response to chemotherapy is often associated with a reduction in TITregs and the recruitment of intratumoral CD8 + T cells [95].…”
Section: Clinical Significance Of Intratumoral Tregsmentioning
confidence: 90%
“…Tumor infiltration by Tregs, near-to-invariably detected by the immunohistochemical detection of FOXP3 + lymphocytes, has been associated with poor prognosis in cohorts of patients affected by multiple distinct neoplasms, including Hodgkin lymphoma, melanoma as well as breast, gastric and ovarian carcinoma [29, [91][92][93][94]. In line with these results, it has been shown that clinical response to chemotherapy is often associated with a reduction in TITregs and the recruitment of intratumoral CD8 + T cells [95].…”
Section: Clinical Significance Of Intratumoral Tregsmentioning
confidence: 90%
“…Schneider et al (30) reported FoxP3 + Treg accumulation and a decrease in the natural killer cells in the center of adenocarcinomas, whereas squamous cell carcinomas displayed less profound accumulation of Tregs. We demonstrated that the number of cCD4 + lymphocytes in adenocarcinomas was significantly higher compared to that in other histological types.…”
Section: Discussionmentioning
confidence: 99%
“…Treg numbers and phenotype in tumor tissues using adjacent lungs as controls (2,33). Use of adjacent tumorfree tissue allows identification of tumor-specific, rather than tissue-specific, differences in Tregs and T cells, as discussed previously (34)(35)(36).…”
Section: Discussionmentioning
confidence: 99%